Eating horses : the evolutionary significance of hippophagy - Levine, Marsha A.
The meat and milk of horses are highly valued food products, past and present. Horses were an especially valuable food resource in grassland habitats, which may explain their increased exploitation in the central Eurasian forest steppe during the late Eneolithic. It may also explain the emphasis on horses in final Upper Palaeolithic art.